(3GdaJM GdQajY aj eOM GdTajYs - (3eMeO Hf eMeO Hf YHO GdefYe GdSYOj , CHhSYO JGL GdOjfs
(3ChdgG (B:s
(3CKfGA MQa GdZjf ef bUjOI HYfhGf(B: (3GdYPH GdeQTha, eWdYgG(B: (3eG aj oaDGOj ef ghGog aQGoZ hMOjK CThGbj Edjg oJSGoZ s
(3BNQgG (B:s
(3Udi GdEdg Ydi GdeNJGQ ef oeVQ eG WGH aj eOMg ef eGOmM bjod s
(3OjhGf TYQ eQJH Ydi GdbhGajs
(3jHOC CKfGA MQa GdZjfs
(3hjfJgj HMQa GddGes
(3hHgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdCOHs